Innovation and trade liberalisation: A case study of the New Zealand deer industry - Chris Nixon (New Zealand Institute of Economic Research (NZIER), 2004)
This paper examines the development of the deer industry as a case study of innovation in a deregulated agricultural environment. The story of deer in New Zealand is remarkable, from an animal released to be hunted for sport, then a pest marked for eradication, to its role as a domesticated farm animal that has contributed significantly to New Zealand economic activity, all within the space of 150 years. We will demonstrate the connection between innovation and commercial success in the deer industry and show how liberal trading regimes (both in the exporting and importing countries) spurred the industry's development. This is particularly relevant for `new' agricultural products (such as venison) because the protectionist infrastructure that is endemic in world agricultural trade does not exist or is not as well-developed in the venison industry.
Keywords: 330; Wild; Tierhaltung; Innovation; Agraraußenhandel; Außenhandelsliberalisierung; Neuseeland